Efek Profil Sudu Turbin Banki terhadap Kekuatan Bahan dan Lintasan Air dalam Runner - Sirojuddin, Sirojuddin; Ibnawati, Regina; Syahri, Junior Ramadhani (Jurnal Rekayasa Mesin, 2021)
In the Banki turbine, the blade profile needs special attention in its design, so that the high output power can be reached. The design of the blade profile is controlled by the strength of the material and water trajectory from the first and second stages of blades to refrain the water strikes the shaft of the turbine. The aim of this study is to determine the effect of the blade profile on the strength of the material and the trajectory of water in the runner to obtain the best blade profile. The strength limit of the material observed from the value of the safety factor and the flow trajectory could be seen from the flow line of water which should not strike the shaft. The number and width of the blades were obtained based on the water discharge of 2 m2/min with a head equal to 5.5 m. 2D and 3D drawings were created using drawing software. Analysis of water trajectories using CFD simulation and stress analysis using FEM software. They were 3 variants of blade profile, variant PS-1 tapered in at top and bottom, PS-2 tapered at top and square in bottom, PS-3 at the bottom with the radius equal to 10 mm while the tip radius is 0.2 mm, and round tip at the top. From simulation results, it was found that the safety factor is 5.36, 4.31, 3.28, for the PS-1, PS-2, PS-3 respectively. From CFD simulation it is proved that PS-3 flow trajectory did not strike the shaft, while the others still strike the shaft and did not meet the safety factor of 3. The variant PS-3 was the best because the safety factor close to 3 and the flow trajectory did not strike the shaft.